Behavior for six years of attacks a human by vampire bats in northern Jalisco, México, after the implementation of a intensive campaign to control this population and its relationship with the existence of refuges and local livestock nearby - Morales Rodríguez, J. A.; González López, A. A.; Rodríguez Cobián, F. J. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
To determine the behavior for six years of attacks on humans by vampire bats in northern Jalisco, Mexico, after the implementation of an intensive campaign to control their population by using an ointment made of warfarin suspended in vaseline ( Vampirinip II), and the relationship of such attacks in the presence of refuges and nearby livestock.